(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Depression is a leading cause of disability and disease worldwide, stress and depression is of public health concernand specially for the breast cancer patient cause short & long term determental effects to the women and her family.This article describe a conceptual framework about the complex relationship between stress, depression & healthoutcomes in breast patient and mindfulness therapy for depression, stress control of these cancer patient may be helpfulfor adding depth to the body of knowledge about the use of mind-body therapies. Mindfulness questionnaire used asa reliable and valid comprehensive for assessing different aspects of mindfulness in breast cancer patient.